Postprandial Fatty Acid Profile, but Not Cardiometabolic Risk Markers, Is Modulated by Dairy Fat Manipulation in Adults with Moderate Cardiovascular Disease Risk: The Randomized Controlled REplacement of SaturatEd fat in dairy on Total cholesterol (RESET) Study. Issue 7 (23rd March 2021) - Markey, Oonagh; Vasilopoulou, Dafni; Kliem, Kirsty E; Fagan, Colette C; Grandison, Alistair S; Sutton, Rachel; Humphries, David J; Todd, Susan; Jackson, Kim G; Givens, David I; Lovegrove, Julie A
ABSTRACT: Background: Chronic consumption of dairy products with an SFA-reduced, MUFA-enriched content was shown to impact favorably on brachial artery flow-mediated dilatation (FMD). However, their acute effect on postprandial cardiometabolic risk biomarkers requires investigation. Objective: The effects of sequential high-fat mixed meals rich in fatty acid (FA)–modified or conventional (control) dairy products on postprandial FMD (primary outcome) and systemic cardiometabolic biomarkers in adults with moderate cardiovascular risk (≥50% above the population mean) were compared. Methods: In a randomized crossover trial, 52 participants [mean ± SEM age: 53 ± 2 y; BMI (kg/m 2 ) 25.9 ± 0.5] consumed a high-dairy-fat breakfast (0 min; ∼50 g total fat: modified: 25 g SFAs, 20 g MUFAs; control: 32 g SFAs, 12 g MUFAs) and lunch (330 min; ∼30 g total fat; modified: 15 g SFAs, 12 g MUFAs; control: 19 g SFAs, 7 g MUFAs). Blood samples were obtained before and until 480 min after breakfast, with FMD assessed at 0, 180, 300, and 420 min. Data were analyzed by linear mixed models. Results: Postprandial changes in cardiometabolic biomarkers were comparable between the different dairy meals, with the exception of a tendency for a 4% higher AUC for the %FMD response following the modified-dairy-fat meals ( P  = 0.075). Plasma total lipid FA analysis revealed that incremental AUC responses were 53% lower for total SFAs, 214% and 258% higher for total cis -MUFAs (predominantly cis -9 18:1), and trans -18:1, respectively, following the modified relative to the control dairy meals (all P < 0.0001). Conclusions: In adults at moderate cardiovascular risk, acute consumption of sequential high-fat meals containing FA-modified dairy products had little impact on postprandial endothelial function or systemic cardiometabolic biomarkers, but a differential effect on the plasma total lipid FA profile, relative to conventional dairy fat meals. This trial was registered at clinicaltrials.gov as NCT02089035.